Nonlinear dynamics of a passively Q-switched Nd:YAG/Cr:YAG laser subject to rectangular wave pump modulation - Sun, Zhaoqi; Bian, Jiayi; Wang, Qiupin; Xia, Guangqiong; Deng, Tao; Lin, Xiaodong; Wu, Zhengmao; Chen, Jianjun; Fan, Li; Gao, Ziye (Laser physics, 2025)
In this work, we theoretically investigate the dynamic behaviors of a passively Q-switched Nd:YAG/Cr:YAG laser under rectangular wave pump modulation. The results show that, fixing the parameter of pump modulation, such as modulation amplitude ( A m ), modulation frequency ( f m ), unmodulated pump rate ( P 0 ) and duty ratio ( DR m ), the passively Q-switched Nd:YAG/Cr:YAG laser can exhibit a variety of nonlinear dynamical behaviors such as period-one (P1), period-two (P2), multi-period and chaotic pulsation. Bifurcation diagrams show that both pulse intensity and pulse frequency display nonlinear dynamics, illustrating an evolution path of quasi-periodic bifurcation. Additionally, mappings uncover the transitions between different dynamic states in the parameter space of the DR m between and other parameters.